Tribo-Mechanical Characteristics of Modified Cu-Cr-Zr Resistance Spot Welding Electrode with Nickel - Ahmad Mostafa; Reham Alhdayat; Rasheed Abdullah (Crystals, 2025)
This study investigates the tribo-mechanical properties of a modified Cu-Cr-Zr alloy with nickel addition, aimed at enhancing its suitability as a resistance spot welding (RSW) electrode material. Two alloy compositions, designated as Sample A (Cu-0.871%Cr-0.156%Zr) and Sample B (modified with 8.94% Ni), were prepared. Microstructural examination revealed a coarse, mixed equiaxed–columnar grain structure in Sample A, while Sample B exhibited a refined dendritic morphology of about 50 μm PDAS, due to nickel-induced solute partitioning, improving microhardness from 72.763 HV to 83.981 HV. The wear behavior was evaluated using a pin-on-disc tribometer with a full factorial design, assessing the effects of rotational speed, load, and time on mass loss and surface roughness. Sample A exhibited increased mass loss and roughness with higher loads and speeds, indicating severe wear. In contrast, Sample B showed reduced mass loss and roughness at higher loads, suggesting a polishing effect from plastic deformation. Design of experiments analysis identified load as the dominant factor for mass loss in Sample A, with speed primarily affecting roughness, while in Sample B, load negatively influenced both responses, with speed–time interactions being significant. These findings highlight the nickel-modified alloy’s superior wear resistance and hardness, making it a promising candidate for RSW electrodes in high-production environments.